Sikap Dan Perilaku Konsumen Minyak Goreng Sawit Di Stadion Maulana Yusuf Serang Banten - Furqon Afif, Ahmad; Ernah (MAHATANI: Jurnal Agribisnis (Agribusiness and Agricultural Economics Journal), 2025)
The rapid growth of the food and culinary industry has been the main factor in the increase in palm oil usage.As part of that industry, fried food vendors in Indonesia also contribute to the increase in palm oil consumption.This study aims to analyze the attitudes and behaviors of street vendors around Maulana Yusuf Stadium in Serang City regarding the consumption of packaged palm oil, as well as the factors that influence their willingness to pay for the product.The research was conducted using a survey method with fried food vendors as respondents.Data were obtained through questionnaires that included respondent characteristics, individual attitudes and subjective norms, and behavioral control.The research results show that individual attitudes, subjective norms, and behavioral control play an important role in shaping the decision to consume packaged palm oil.This research provides insights into the dynamics of palm oil consumption among street vendors and the implications for business actors and policymakers in meeting consumer needs.